Consumption taxation and endogenous growth in a model with new generations - Alberto Petrucci (Fondazione Eni Enrico Mattei (FEEM), 2001)
This article studies the implications of consumption taxation on capitalaccumulation in a one-sector endogenous growth model with finite horizons. A tax on consumption, when tax revenues are lump-sum rebated to consumers, redistributes income between living generations and future, still unborn, generations, and therefore depresses aggregate consumption and raises saving, stimulating capital accumulation and economic growth. If however the resources from taxation are used for financing unproductive public spending, the effect of the consumption tax on the endogenous growth rate disappears as no intergenerational redistribution of income occurs. Finally, a consumption tax hike accompanied by a compensatory reduction of public debt increases long-run economic growth and reduces the consumption-output ratio. Our results on consumption taxation differ substantially from those obtained within the endogenous growth literature.
Keywords: H24; O41; 330; Consumption tax; endogenous growth; overlapping generations; Verbrauchsteuer; Neue Wachstumstheorie; Overlapping Generations; Theorie